The innovation imperative : architectures of vitality - Brown, Pia Ednie; Burry, Mark.; Burrow, Andrew (London : John Wiley & Sons, Inc., 2013)
Suggesting a process that is fundamentally emergent, collective and environmentally situated, this book explores architectural innovation in terms of the production of vitality.
EditorIal 5 Helen Castle About the Guest Editors 6 Pia Ednie-Brown, Mark Burry and Andrew Burrow Introduction 8 The Innovation Imperative: Architectures of Vitality Pia Ednie-Brown, Mark Burry and Andrew Burrow The Ethics of the Imperative 18 Pia Ednie-Brown Design and Society: Innovation Through Appropriation and Adaptation 24 Mark Burry Innovation at the Storefront: The Practice of Eva Franch i Gilabert 34 Pia Ednie-Brown Architecture as Initiative (A Manifesto) 38 Veronika Valk On a Fine Line: Greg Lynn and the Voice of Innovation 44 Pia Ednie-Brown Becoming Architectural: Affirmative Critique, Creative Incompletion 50 Brian Massumi The Ebb and Flow of Digital Innovation: From Form Making to Form Finding and Beyond 56 Mario Carpo Strange Vitality: The Transversal Architectures of MOS and New Territories/R&Sie(n) 62 Pia Ednie-Brown The Vitality of Matter and the Instrumentalisation of Life 70 Oron Catts and Ionat Zurr Initiating Change: Architecting the Body-Environment with Arakawa and Gins 76 Jondi Keane bioMASON and the Speculative Engagements of Biotechnical Architecture 84 Pia Ednie-Brown The Evolutionary Dynamics of Sentience in Cities 92 Michael Weinstock Final Draft: Designing Architecture s Endgame 98 Gretchen Wilkins and Andrew Burrow Differentiation in Vital Practice: An Analysis Using RMIT University of Technology and Design Interfaces With Architects 106 Leon van Schaik The Mothers of Invention 114 Tom Daniell Designing Tomorrow s Innovation 124 Terry Cutler Counterpoint 128 Architecture, Innovation and Tradition Antoine Picon Contributors 134
"January/February 2013."
Includes bibliographical references.
Keywords: Architectural design -- 21st century